Community Empowerment: Training on Cultivation of Mushroom From Corncob’s Waste In Air Terang Village, Central Sulawesi - Rewang Febri Pangestuti; Erna Wijayanti; M Rikza Chamami (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The community has not utilized the abundant corncob waste in Air Terang Village. Corncob waste can be used as a medium for growing mushrooms. This program service aims to improve the knowledge and skills of the community in Air Terang Village, Tiloan District, Buol Regency in cultivating mushrooms from corncobs. The implementation of this service uses the Participatory Action Research (PAR) method, which consists of three stages: preparation, implementation, and evaluation. The result of this community service program is the community begins to understand and realize the use of corncob waste as a medium for growing mushrooms and can cultivate mushrooms from corncobs. Recommendations for the next service program are mushroom post-harvest processing and training on mushroom marketing strategies.